China's Rule of Law Index 2017 (Research Series on the Chinese Dream and China's Development Path,, 2018)
This book investigates and evaluates the indexes of Government Transparency, Judicial Transparency, Procuratorial Transparency, and Legislation by Local People's Congresses in China. It explores a representative case study on the Rule of Law in Yuhang District of Hangzhou City, assesses the progress made and remaining problems in the implementation of these systems, and puts forward suggestions on how they could be improved in the future.